Pengaruh Lingkungan Kerja Dan Pengembangan Karyawan Terhadap Kepuasan Kerja Karyawan Pada Bank BTN (Persero) Cabang Karangasem - Megawati Megawati (RELASI : JURNAL EKONOMI, 2021)
The research is conducted in order to analyze the influence of working environment, employee development toward work satisfaction in BTN Bank (Persero) Karangasem to obtain of more deep influence of employee development ,working environment toward worked satisfaction in BTN Bank (Persero) Karangasem. Data is analyzed constructively by using the technique analyze the simple regression and multiple regression analysis. Research location is the employee in BTN Bank (Perswero) Karangasem The method of this research is simple random sampling, that taken 55 Operational Division employee at Transaction Process Division, Loan Administration Division, and General Administration Division, while data collecting by using questionnaire and cultivated using SPSS 19.0. The result of t test for working environment is 2.123, and the signification is 0.038. This shows that there is an effect between working environment toward job satisfaction. The result of t test for employee development is -2.160 ,and the signification is 0.035 This shows that there is an effect between employee development toward job satisfaction. The result of F test is 5.798, and the signification is 0.005. This shows that there is an effect between working environment and employee development toward job satisfaction. The result of R2 is 0.182 or 18,2%. It means Job Satisfaction is affected by working environment and employee development as much as 18,2%. Keywords: working environment, employee development, job satisfaction